OPTIMALISASI PARTISIPASI MASYARAKAT DALAM MENCAPAI KEUNGGULAN PROGRAM MKSB (Magelang Kota Sejuta Bunga) - Eny Boedi Orbawati; Retno Rusdjijati; Yun Arifatul Fatimah; Oesman Raliby; Didin Saepudin; Awaluddin Setya Aji; Doddy Ardjono; Andreas Pandiangan; Arizal Arizal; Agus Setyowidodo (Jendela Inovasi Daerah, 2021)
The purpose of the preparation of this policy text is to identify the factors that cause the 2015-2018 period of 2015-2018 less than optimal performance of the Magelang City of a Million Flowers (MKSB) program. MKSB is a slogan that supports the branding of Magelang City. This program has been implemented for two periods, namely the period 2012-2015 and the period 2015-2018. Evaluation results from various sources indicate that the quality of human resources for implementing the MKSB program and community participation in supporting the program is still low. After conducting a study, it was shown that the 2 obstacles were caused, among others, by the low participation of the community to support the program, so that the community might not feel they belonged to this program which had an effect on low awareness. Therefore, solutions are offered through more targeted community empowerment, the formation of industrial clusters, and the formation of flower clusters.